OPTIMASI PEMASARAN PRODUK PANGAN LOKAL MELALUI PELATIHAN TEKNOLOGI BERBASIS WEB DI CV TOTALINDO GEMILANG - Hardyanto, R Hafid; Jerimia Fitriani, Rosmauli; Hasanati Marfuah, Hasti; Venti Yoanita, Yulia (Intimas, 2024)
Local food small and medium industries (SMIs) in Indonesia have great potential to grow, one of which is CV Totalindo Gemilang. CV Totalindo Gemilang is a business engaged in the production of traditional drinks made from spices or empon-empon. CV Totalindo Gemilang has great potential to grow in Indonesia, but is still constrained in the marketing aspect. Currently, marketing is still done conventionally. Lack of knowledge and skills in utilizing information and communication technology (ICT) is one of the inhibiting factors. The solution to this problem is to conduct web-based technology training to optimize the marketing of local food products at CV Totalindo Gemilang. The training used lecture, demonstration, and hands-on methods. The participants were trained to create and post articles on beverage product promotion through CV Totalindo Gemilang's web site. In this training, participants managed an online store, and built website interactions to promote their products. The results of the training showed that the participants have better knowledge and skills in utilizing web technology, especially in managing the CV Totalindo Gemilang web site. They can manage the online store, fill in articles, and fill in the products marketed on the website.